Peningkatan Kompetensi Guru SMP Muhammadiyah 12 Gresik dalam Merancang Pembelajaran yang Mendukung Kompetensi 6C Siswa - Suryanti, Sri; Damayanti, Nia Wahyu; Standsyah, Rahmawati Erma; Arifani, Yudhi (Jurnal SOLMA, 2024)
Background: This community service activity is driven by three factors: 1) the significance of the teacher's role in cultivating student competencies aligned with 21st-century demands; 2) education's emphasis on not only academic mastery but also the cultivation of comprehensive skills; 3) the 6C framework (Critical Thinking, Creativity, Collaboration, Communication, Citizenship, and Character) serves as the fundamental basis for equipping students to confront escalating global challenges. This service activity aims to enhance comprehension and proficiency in designing learning that fosters the competencies of 6C students. Method: The participants in this initiative comprise 32 educators from Gresik Middle School. The program is executed in phases: 1) Reinforcement of the 6C concept; 2) A workshop on learning design that facilitates 6C; 3) Independent implementation and evaluation without external support. Results: The findings indicated an enhancement in educators' comprehension of crafting learning activities that promote competency 6C. Moreover, it pertains to teachers' capacity to devise 6C learning experiences. 80% of teachers can construct learning activities classified as good, while the remainder falls into the fairly good group. Teacher Competency Enhancement Program To effectively construct learning activities for 6C students, it is essential to consistently engage with the school's learning community. It is essential for the teacher to remain informed about the latest pedagogical strategies, enabling the adaptation of instructional methods to meet student developmental needs and evolving circumstances, while also enhancing collaboration among educators through discourse and the exchange of best practices within the learning community